10 P Pediatrics: notes for the future - Fanos, Vassilios (Journal of Pediatric and Neonatal Individualized Medicine (JPNIM), 2016)
In the last few years medicine has been changing radically, almost as a kind of metamorphosis. The final goal of this editorial, which we may call a "manifesto" that illustrates where we would like, or perhaps where we want to go, is to improve the wellbeing of each single patient rather than limiting ourselves to curing their disease. This decalogue of the change applies even more to pediatrics and will make possible the 10 P Pediatrics, as recently defined: personalized, perspective, predictive, preventive, precise, participatory, patient-centric, psycho-cognitive, postgenomic and public. In a word: individualized medicine.